PENGARUH SENAM TERHADAP PENURUNAN KADAR GULA DARAH PADA PENDERITA DM TIPE 2 DI PUSKESMAS PAKIS SURABAYA - Lono Wijayanti; Ghady Anggun M (Universitas Nahdlatul Ulama Surabaya, 2013)
The type of sport suggested for Diabetes Mellitus patient is Diabetes Gym, but most societies, especially diabetes mellitus patients are lazy to do it. On diabetes mellitus type 2, diabetes gym acts as glycemic control which manages and control blood sugar rate. This research purposes to know diabetes gym influence toward the decrease of blood sugar rate on Diabetes Mellitus patient type 2 in Puskesmas Pakis Surabaya. This research used quasy experiment design. Total of the population of all Diabetes Mellitus patients type 2 is 28 respondents taken by probability sampling - simple random sampling technique; 14 respondents in control group and 14 respondents in treatment group. The independent variable is Diabetes Gym and the dependent variable is the decrease of blood sugar rate. Data are collected by using Glucometer, striptest, needle and observation sheet. Data are analyzed by using Wilcoxon signed rank test with α < 0.05. The result of this research shows that almost all of the respondents in the treatment group have a good category of blood sugar decrease after performing gym, meanwhile almost all of the respondents in control group that do not perform gym have an adequate category of blood sugar decrease. Then, the result is analyzed by Wilcoxon signed rank test and obtained ρ (0,019) < α (0,05) so H0 is refused. It means that there is an influence of diabetes gym to the decrease of blood sugar on the Diabetes Mellitus patients type 2 in Puskesmas Pakis Surabaya. Performing Diabetes Gym influences in decreasing blood sugar rate. Therefore, nurse can take a part in leading diabetes patients to perform diabetes gym so it can be used as the therapy in controlling and decreasing blood sugar rate.